Cerebellar haematomas caused by angiomas in children - Erenberg, G. (1972)
Spontaneous cerebellar haematomas in previously well children are most often caused by haemorrhage from small angiomas. Eight such cases in children 12 years of age or younger have been reported previously. Their clinical course was usually not as acute as the course most commonly seen in adults, and four of the children survived after evacuation of the haematoma. Two additional cases are presented. Both children were admitted in a comatose state, but survived after surgical intervention. Cerebellar haematomas in children seem to have a better prognosis than in adults and should be considered in the evaluation of children with subarachnoid haemorrhage or the rapid onset of coma. Even if admitted in extremis, recovery is possible after prompt diagnosis and surgical evacuation of the haematoma.